Chinese Historical Thinking : An lntercultural Discussion - Time Kragh, Ulrich; Huang, Chun-chieh; Rüssen, Jörn (2015)
The book presents Chinese historical thinking by four articles. It is covered the ancient origin and the development to modernity and is commented by seven international experts. Presentation and comments find ›second thought‹ by three other international scholars, and at the end the whole discussion find an answer by the authors of the first presentations. The complex structure of argumentation documents not only various ideas and interpretations of Chinese historical thinking, but represent the possibilities and problems of intercultural comparison at the same time.